The Influence of The Cooperative Script Method on The German Reading Ability of Class XI IPS Student at SMA Negeri 5 Pematang Siantar - Mei Rani Sibuea; Insenalia S.R Hutagalung; Tarida Alvina Simanjuntak (MultiTech Publisher, 2023)
This research aims to see the effect of the Cooperative Script method on the German reading ability of class XI IPS students at SMA Negeri 5 Pematang Siantar. The research method used is quantitative with Pre-experimental research type and One Group Pretest-Posttest research design . The research population was class XI IPS of SMA Negeri 5 Pematang Siantar as many as 167 people. Based on the probability sampling technique with simple random sampling type, 32 people were produced from the population, namely class XI IPS-4 as the research sample. The data collection technique is in the form of a German text reading test. By carrying out the pretest, treatment stages by applying the Cooperative Script learning method and posttest , research data was produced.